English Teachers’ Challenges in Integrating Technology on Online Classroom of Madrasah Aliyah at Suburban Area in Maros during COVID-19 Pandemic - Sitti Nurjannah; Andi Ainur Akbar (Edumaspul: Jurnal Pendidikan, 2023)
Following the COVID-19 pandemic, social distancing became a necessity, resulting in a shift away from traditional classroom-based learning and toward technology-based learning. This research aims to find out the integration of technology and challenges that teacher faced during online classroom. This research used descriptive-qualitative approach with 11 English teachers who teach at 8 Madrasah Aliyah in suburban area of Maros participated in the research. The instruments used to collect the data were open-ended questionnaire and semi-structured interview. The findings show that teachers: 1) integrated technology by utilizing applications such as using WhatsApp Messenger and Google Classroom in the teaching and learning process, 2) teaching English language skills by providing materials in the form of voice notes, videos, files, and photos, 3) presented the materials in attractive manner, 4) collaborated on teaching materials from various internet sources. However, the integration of this technology was still not optimal, such as the absence of face-to-face virtual interactions, the lack of use of technology in understanding English skills, and non-specific sources of materials. The lack of integration of technology experienced by teachers was caused by the challenges they faced, such as: technological inhibition, infrastructure limitation, disturbance in execution, state of mind, and hiatus between people.